(untitled) (Canadian Medical Education Journal, 2018)
Background: Physicians often fail to implement clinical practice guidelines. Our aim was to evaluate whether a purposefully sequenced, multifaceted educational intervention would increase physician adherence to a guideline for voiding cystourethrogram (VCUG) use following first urinary tract infection (UTI) in young children. Methods: Using a single centre, pretest-posttest design, we compared the proportion of guideline adherent VCUG orders and the VCUG ordering rate before and after three educational interventions (interactive lecture, clinical pathway, faxed reminder) selected and sequenced according to the PRECEDE (Predisposing, Reinforcing and Enabling Constructs in Educational Diagnosis and Evaluation) health promotion model. Results: One hundred and nine physicians ordered 219 VCUGs for 219 children. Following the interventions, there was an increase in the monthly proportion of adherent VCUGs ordered by pediatricians (analysis of variance (ANOVA) F(2,29) = 3.38, p = .048) and non-pediatricians (ANOVA F(2,28) = 14.71, p < .001). Also, pediatricians decreased their monthly VCUG ordering rate (linear trend incidence rate ratio 0.74, 95% confidence interval (CI) [0.54, 0.99]). Pediatricians were more likely to adhere with the guideline than were non-pediatricians (odds ratio 2.91, 95% CI [1.5, 5.5]). Conclusion: Exposure to purposefully sequenced educational interventions based on the PRECEDE model was associated with increased adherence to guideline recommendations.